Fabrication and properties of cordierite / anorthite composites. Issue 8 (1st June 2017) - Naga, Salma M.; Sayed, M.; Elmaghraby, H.F.; Khalil, M.Sh.; EL-Sayed, M.A.
Abstract: The designed cordierite/anorthite batch compositions were studied to gain the favorable properties of both materials where, cordierite has low thermal expansion coffecient and high strength than anorthite.Low cost starting materials such as sugar beat filter cake and talc carbonate were used in the present study. Examination of the effect of cordierite addition (in the range of 10-25mass-%) on the physical, mechanical, electrical and thermal expansion coefficient properties as well as the phase composition and microstructure for the fabricated cordierite/anorthite composites were carried out. The results reveal that the increase in the cordierite content up to 20 mass-%, improves the sinterability and electrical properties. In addition, it increases the bending strength, hardness and decreases the thermal expansion coffecient. However, further increase in the cordierite content up to 25 mass% has negative influence on the physical, electrical and mechanical properties of the cordierite/anorthite composites.